Superiority of directly administered antiretroviral therapy over self-administered therapy among HIV-infected drug users: a prospective, randomized, controlled trial. - Altice, Frederick L; Maru, Duncan Smith-Rohrberg; Bruce, R Douglas; Springer, Sandra A; Friedland, Gerald H (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2007)
Directly administered antiretroviral therapy (DAART) is one approach to improve treatment adherence among human immunodeficiency virus (HIV)-infected drug users.
Keywords: Adult; Antiretroviral Therapy, Highly Active; Directly Observed Therapy; Female; HIV Infections; HIV-1; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Patient Compliance; Prospective Studies; RNA, Viral; Self Administration; Substance-Related Disorders; Treatment Outcome